Implementation of Agile Adoption Best Practice (Study Case In PT Telkom Indonesia) - Firza Syafitrah; Andi Wijayanto; Hari Susanta Nugraha (Universitas Diponegoro, 2024)
Abstract The rapid development of telecommunications in the world means that all telecommunications companies must be able to continue to develop and adapt according to market needs. This research uses three main indicators as reference material for analysis, namely team dynamics and activities, program operations, and organizational environment. This research is a qualitative research with a literature review of scientific articles and company reports with discussions related to company transformation, especially the Five Bold Moves with the implementation of agile adoption best practice. The findings show that good implementation of agile adoption best practices can support the system or transformation strategy of telecommunications companies in Indonesia, namely PT Telkom Indonesia. Implementation of a strategic transformation program through Five Bold Moves by implementing agile adoption best practices in its implementation is the key to the transformation process to obtain maximum processes and results. The results of this research can be developed by continuing to pay attention to the implementation process of the DigiCo program, which is one of the Five Bold Moves that has not been implemented.Keywords: Agile; Agile Organization System; Agile Adoption Best Practice; Five Bold Moves; Corporate Transformation